Implementasi Metode K-Means Clustering Untuk Menentukan Tingkat Peminatan Konsumen Terhadap Type Smartphone Di Tio Cell Dan Tio Cell 2 - Bomanthara .; R.M. Nasrul Halim (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Smartphone is a tool to communicate and a tool to access the internet that makes it easier for users to find information. At this time, smartphones are very loved by the community, even for most people, smartphones are made as basic needs. With a fairly large interest in smartphones, the sales figures for smartphones themselves are certainly very high. In this case, the researcher will conduct a study to determine the interest in smartphone brands for the last three years, taking place at Tio Cell and Tio Cell 2, located in Lubuk Linggau City. This study uses the K-Means Clustering method, in which K-Means Clustering is a method for finding and grouping data that have similar characteristics (similarity) between one data and another. Sales data from both outlets will be processed using the calculation methods and formulas in K-Means Clustering, then it will produce the most desirable and uninterested smartphone types, which will be divided into several groups (clusters) so that the results are more valid. Sales will also be processed using RapidMiner Studio software. The results of this study are expected to be used as an example of the utilization of sales data in Tio Cell and Tio Cell 2. Keywords—Smartphone type specialization, Data Mining, Clustering, K-Means method, RapidMiner Studio.